2022
DOI: 10.3389/fphar.2022.790136
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides, Next Potential Agent for the Treatment of Epilepsy?

Abstract: Epilepsy is a chronic neurological disorder. Current pharmacological therapies for epilepsy have limited efficacy that result in refractory epilepsy (RE). Owing to the limitations of conventional therapies, it is needed to develop new anti-epileptic drugs. The beneficial effects of polysaccharides from Chinese medicines, such as Lycium barbarum polysaccharides (COP) and Ganoderma lucidum polysaccharides (GLP), for treatment of epilepsy include regulation of inflammatory factors, neurotransmitters, ion channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Such pathophysiological pathway could be an interesting target to G. lucidum compounds, especially polysaccharides. Besides, although these compounds are not capable of crossing the blood–brain barrier, the polysaccharides can modulate peripheral inflammation, oxidative stress, or even intestinal dysbiosis 66 . We highlight the need for studies involving the modulating effect of G. lucidum components on dysbiosis, as this mushroom is accepted as a nutraceutical element and the evidence of the polysaccharides in the regulatory function of the intestinal microbiota 66 …”
Section: Neuroprotective Effects Preventing Memory Impairmentsmentioning
confidence: 97%
See 4 more Smart Citations
“…Such pathophysiological pathway could be an interesting target to G. lucidum compounds, especially polysaccharides. Besides, although these compounds are not capable of crossing the blood–brain barrier, the polysaccharides can modulate peripheral inflammation, oxidative stress, or even intestinal dysbiosis 66 . We highlight the need for studies involving the modulating effect of G. lucidum components on dysbiosis, as this mushroom is accepted as a nutraceutical element and the evidence of the polysaccharides in the regulatory function of the intestinal microbiota 66 …”
Section: Neuroprotective Effects Preventing Memory Impairmentsmentioning
confidence: 97%
“…Regarding inflammatory pathways, an increase in the Gram‐negative bacteria population seems to result in mild chronic inflammation, affecting the homeostasis of the intestinal epithelium, which increases the permeability to the leakage of bacterial toxins into the systemic circulation, contributing to mechanisms of neuroinflammation, oxidative stress, neuronal apoptosis, which constitute the pathophysiology of cognitive disorders, such as AD 67 . In vitro studies reported that G. lucidum oligosaccharides increase the amount of beneficial (i.e., Lactobacillus , Bifidobacterium , Faecalibacterium , and Prevotella ) and decrease the relative abundance of noxious bacteria (i.e., Escherichia , Shigella , and Dorea ), contributing to health gut and preventing dysbiosis 66,68 . In addition, studies demonstrated that polysaccharides with different molecular weights inhibit the secretion of proinflammatory cytokines (i.e., TNF‐α, IL‐1β, and IL‐6) in the inflammation model induced by lipopolysaccharides in human colorectal adenocarcinoma cells (pretreatment for 2 h at final concentrations of 10, 50, and 200 µg/mL) and in mice dextran sulfate sodium‐induced colitis (pretreatment at doses 10, 50, and 200 mg, for 7 days), recovering inflamed mice colonic tissues 69 …”
Section: Neuroprotective Effects Preventing Memory Impairmentsmentioning
confidence: 99%
See 3 more Smart Citations